FGFs: Neurodevelopment’s Jack-of-all-Trades – How Do They Do it? - Hebert, Jean M. (Frontiers in Neuroscience, 2011)
From neurulation to postnatal processes, the importance of FGF signaling in many aspects of neural precursor cell biology has been well documented. However, identifying a need for FGFs in a neurogenic process provides only an initial and superficial understanding of what FGF signaling is doing. How FGFs specify cell types in one instance, yet promote cell survival, proliferation, migration, or differentiation in other instances remains largely unknown and is key to understanding how they function. This review describes what we have learned primarily from in vivo vertebrate studies about the roles of FGF signaling in neurulation, anterior-posterior patterning of the neural plate, brain patterning from local signaling centers, and finally neocortex development as an example of continued roles for FGFs within the same brain area. The potential explanations for the diverse functions of FGFs through differential interactions with cell intrinsic and extrinsic factors is then discussed with an emphasis on how little we know about the modulation of FGF signaling in vivo. A clearer picture of the mechanisms involved, however, is nevertheless essential to understand the behavior of neural precursor cells and to potentially guide their fates for therapeutic purposes.